Links between Main Frequencies of Established Rotating Stall and Rotational Frequencies and/or Blade Passing Frequencies - Yeshayahou Levy; Asaf Modelevsky; Joseph Pismenny; Jens Friedrichs; Detlev Wulff (International Journal of Rotating Machinery)
The ratios between the main frequency of rotating stall and rotational frequency may be considered in the form of exact ratios of small natural numbers if the pressure signals in compressors during rotating stall include the rotor rotation frequency component. During rotating stall in compressors with good rotor balancing (with absence of the rotational frequency component in the frequency characteristics of pressure signals), these ratios between the main frequency of rotating stall and rotational frequency are or are not in the form of ratios of small natural numbers. The experimentally received characteristics of power spectral density of pressure signals also show the presence of components with combinations of blade passing frequency and different harmonics of main rotating stall frequency.